Aeromonas species isolated from aquatic organisms, insects, chicken, and humans in India show similar antimicrobial resistance profiles - Dubey, Saurabh; Ager-Wick, Eirill; Kumar, Jitendra; Karunasagar, Indrani; Karunasagar, Iddya; Peng, Bo; Evensen, Øystein; Sørum, Henning; Munang’andu, Hetron M. (Frontiers in Microbiology, 2022)
Aeromonas species are Gram-negative bacteria that infect various living organisms and are ubiquitously found in different aquatic environments. In this study, we used whole genome sequencing (WGS) to identify and compare the antimicrobial resistance (AMR) genes, integrons, transposases and plasmids found in Aeromonas hydrophila, Aeromonas caviae and Aeromonas veronii isolated from Indian major carp (Catla catla), Indian carp (Labeo rohita), catfish (Clarias batrachus) and Nile tilapia (Oreochromis niloticus) sampled in India. To gain a wider comparison, we included 11 whole genome sequences of Aeromonas spp. from different host species in India deposited in the National Center for Biotechnology Information (NCBI). Our findings show that all 15 Aeromonas sequences examined had multiple AMR genes of which the Ambler classes B, C and D β-lactamase genes were the most dominant. The high similarity of AMR genes in the Aeromonas sequences obtained from different host species point to interspecies transmission of AMR genes. Our findings also show that all Aeromonas sequences examined encoded several multidrug efflux-pump proteins. As for genes linked to mobile genetic elements (MBE), only the class I integrase was detected from two fish isolates, while all transposases detected belonged to the insertion sequence (IS) family. Only seven of the 15 Aeromonas sequences examined had plasmids and none of the plasmids encoded AMR genes. In summary, our findings show that Aeromonas spp. isolated from different host species in India carry multiple AMR genes. Thus, we advocate that the control of AMR caused by Aeromonas spp. in India should be based on a One Health approach.